O que resta da criminologia crítica - Zilio, Jacson (2015)
This article seeks to analyze the history of criminology, since its birth, strolling by racist prevailing, social and radical, to everyday life new criminology. In this path, it seeks to highlight the contributions of labeling approach theory and mainly critical criminology, to thus extract a realist and alternative criminal policy, which can serve as critical fundament of criminal law.